On Legitimacy Crises and the Resources of Global Governance Institutions: A Surprisingly Weak Relationship?. Issue 3 (24th June 2019) - Bes, Bart Joachim; Sommerer, Thomas; Agné, Hans
Abstract: While scholars commonly assume that Global Governance Institutions (GGIs) need legitimacy to perform effectively, there are few systematic empirical studies assessing the consequences of legitimacy (or the lack thereof) for the functioning of GGIs. Inspired by the new institutionalism in organization theory, which predicts that more legitimate organizations will get more resources than illegitimate ones, we look into how legitimacy affects the resourcing of GGIs. We assess how crises of legitimacy affect the staff and financial resources of 21 GGIs from 1985 to 2015. Multivariate statistical analysis suggests that the effects of legitimacy crises on GGI resourcefulness are interesting but surprisingly weak, often GGI specific, and dependent on time and the source of the challenge. Specifically, we find that elite criticisms of GGIs lead to deep resource cuts in the short and medium term, while the effect of mass protests takes longer. The paper concludes by setting an agenda for further theorizing and empirical testing of the consequences of legitimacy in global governance. Abstract : We find that elite criticisms of GGIs lead to deep resource cuts in the short and medium term, while the effect of mass protests takes longer.